(untitled) (مجلة العلوم الشاملة, 2026)
This study presents the first comprehensive thermodynamic evaluation of a 350 MW reheat steam unit at the Al‑Khalij Thermal Power Plant in Sirt, Libya. Energy and exergy analyses were applied to assess component‑wise performance under full‑load operating conditions and to examine the influence of ambient temperature variations typical of Mediterranean coastal environments. The results demonstrate that the steam generator (boiler) is the principal source of irreversibility, accounting for approximately 88% of total exergy destruction. This high level of destruction is primarily attributed to combustion processes and the significant temperature gradients across heat transfer surfaces. In contrast, the turbine system exhibited strong performance, achieving an exergetic efficiency of 86.3%, which reflects the advantages of modern reheat parameters in maximizing work output and minimizing moisture losses. Regenerative feedwater heaters and auxiliary pumping systems also performed efficiently, with efficiencies ranging between 71% and 96%, thereby contributing to cycle stability. The condenser, while associated with substantial energy rejection, contributed only 3.6% of total exergy destruction due to the inherently low quality of the rejected heat. Sensitivity analysis revealed that increasing the reference environment temperature from 283 K to 303 K leads to a slight decline in boiler and turbine efficiencies, while condenser efficiency improves under the same conditions. Overall, the Al‑Khalij unit achieved an exergetic efficiency of 30.3%, a value consistent with contemporary reheat steam cycles. These findings establish a benchmark for Libya’s thermal generation sector, identify the boiler as the most critical area for improvement, and provide practical guidance for enhancing efficiency in large‑scale power plants operating under Mediterranean environmental conditions.